Theories for a pedagogical consulting - Claudio Melacarne (Firenze University Press, 2020)
This paper aims to explore some theoretical frameworks that could be used to support a advanced reflection on pedagogical consulting approach. Three ways of dissertations will be used. The first, the epistemological conditions of the discourse on pedagogical counseling. The second, the pedagogical roots of the educational consulting process and, the third, the development of pedagogical consulting in a critical way.   Prospettive teoriche per la consulenza pedagogica. Il presente contributo intende esplorare alcune direttrici teoriche che sembrano poter essere utilizzate per avviare una riflessione matura sulla consulenza pedagogica. Verranno seguite tre piste di argomentazione. La prima si concentrerà sulle condizioni epistemologiche del discorso scientifico sulla consulenza pedagogica, la seconda sulle radici pedagogiche della consulenza e la terza sulle potenziali aree di sviluppo di questa area di crescente interesse.